1999
DOI: 10.1210/endo.140.6.6625
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Activation Functions of the Sp-Related Nuclear Factor, Basic Transcription Element-Binding Protein, and Progesterone Receptor in Endometrial Epithelial Cells*

Abstract: The present study examined the trans-activation potential of basic transcription element-binding protein (BTEB), a recently identified member of the Sp family of GC box-binding transcription factors, on the expression of the gene encoding the pregnancy-associated, epithelial-specific, and progesterone (P)-induced porcine uterine endometrial secretory protein, uteroferrin (UF). Endometrial expression of BTEB, P receptor (PR), and UF genes was analyzed by RT-PCR as a function of pregnancy stage and cell type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…We also showed that BTEB1 transactivates gene promoters containing GC-rich recognition motifs (25,26), but in the presence of ligand-activated PR-B, the functional complex formed between the PR-B dimer and BTEB1 favored the induction of PRE-containing promoters (24). Because the relative levels of PR-A, PR-B and BTEB1 are tightly regulated in normal uterine endometrium, and deviations in PR isoform ratios can affect tissue responsiveness to P, we examined whether BTEB1 alters the transactivity of PR-A for different promoters.…”
mentioning
confidence: 74%
“…We also showed that BTEB1 transactivates gene promoters containing GC-rich recognition motifs (25,26), but in the presence of ligand-activated PR-B, the functional complex formed between the PR-B dimer and BTEB1 favored the induction of PRE-containing promoters (24). Because the relative levels of PR-A, PR-B and BTEB1 are tightly regulated in normal uterine endometrium, and deviations in PR isoform ratios can affect tissue responsiveness to P, we examined whether BTEB1 alters the transactivity of PR-A for different promoters.…”
mentioning
confidence: 74%
“…Quantitative determination of luciferase activity (measured as relative light units) in the cell lysates was normalized to the protein concentration of cell lysate. 36 …”
Section: Reporter Gene Assaysmentioning
confidence: 99%
“…Sp1 physically and functionally interacts with several nuclear receptor superfamily proteins including ER␣ (53)(54)(55)(56)(57)(58)(59)(60)(61)65), retinoic acid receptors, chicken ovalbumin upstream promoter transcription factor (COUP-TF), and steroidgenic factor-1, and the progesterone receptor interacts with Sp1 and basal transcription element binding protein (an Sp family member) to modulate gene expression through GC-rich promoter elements (93)(94)(95)(96)(97)(98)(99). This paper describes a novel ER␣/Sp3 pathway for hormone-mediated decreased gene expression through a G/GCrich element in the VEGF gene promoter, and this mechanism may be important for hormone-mediated down-regulation of other genes.…”
Section: Transactivation Of Pvegf6 By Er␣/sp1 and Er␣/sp3 In Schneidementioning
confidence: 99%